A history of depression with psychotic features modifies a woman's risk for depression after childbirth. Issue 3 (2nd July 2020) - Silverman, Michael E.; Goldstein, Martin A.; Smith, Lauren; Reichenberg, Abraham; Lichtenstein, Paul; Sandin, Sven
ABSTRACT: Objective: Postpartum depression (PPD) is a prevalent disorder that can result in negative child developmental outcomes. While a maternal history of unipolar depression is understood to be the largest risk factor, how a history of unipolar depression with psychotic features modifies PPD risk remains unclear. Methods: In a prospective cohort of all women with single infant births in Sweden, 1997–2008, the study explored the relative risk (RR) of PPD for mothers with a depression history, both with and without psychotic features. Results: Of the 707, 701 mothers observed, 4, 397 received a PPD diagnosis (62 per 10, 000). PPD incidence in women without a depression history was 48 per 10, 000 compared to 1, 154 per 10, 000 for those with a depression history (RR = 27.0). The incidence of PPD in women with a depression history that included psychotic features was 2, 360 per 10, 000 (RR = 37.9). Conclusion: PPD risk is significantly elevated among women who had a history of depression with psychotic features compared to women with a history of depression without psychotic features.